2022
DOI: 10.1039/d1ta10707k
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in organic solar cells based on non-fullerene acceptors: materials to devices

Abstract: Harnessing energy from the sun is attracting increasing attention as the traditional fossil-based energy sources are being depleted. Photovoltaics (PV) is now an established technology and the most promising method...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
88
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(98 citation statements)
references
References 283 publications
(242 reference statements)
0
88
0
Order By: Relevance
“…Researchers have proposed various strategies for stable operation of OSCs based on NFAs. 160 In order to increase the intrinsic chemical and photochemical stability of A-D-A type NFAs, Liu et al 161 employed cyclohexene as π-conjugated bridges between electron donor unit and electron withdrew unit, and obtained a series of ring-locked NFAs. The PTB7-Th:IDTT-CT based OSCs showed very encouraging photostability, the PCE of which could retain over 80% of its initial PCE in air after one sun irradiation without UV filter for 200 h. Holliday et al 106 present a new SM-NFA named O-IDTBR which is based on an indacenodithiophene core with benzothiadiazole and rhodanine flanking groups.…”
Section: Stabilitymentioning
confidence: 99%
“…Researchers have proposed various strategies for stable operation of OSCs based on NFAs. 160 In order to increase the intrinsic chemical and photochemical stability of A-D-A type NFAs, Liu et al 161 employed cyclohexene as π-conjugated bridges between electron donor unit and electron withdrew unit, and obtained a series of ring-locked NFAs. The PTB7-Th:IDTT-CT based OSCs showed very encouraging photostability, the PCE of which could retain over 80% of its initial PCE in air after one sun irradiation without UV filter for 200 h. Holliday et al 106 present a new SM-NFA named O-IDTBR which is based on an indacenodithiophene core with benzothiadiazole and rhodanine flanking groups.…”
Section: Stabilitymentioning
confidence: 99%
“…[6][7][8] To make use of p-conjugated systems based on their light absorbance, carrier transport, and ease of frontier energy level, the donor-acceptor (D-A)-type conguration has become a rational molecular design for both the donor and acceptor. [9][10][11][12][13][14][15][16] The development of A-D-A-type nonfullerene acceptors (NFAs) with large fused-ring donor structures, such as Y6 and ITIC, have signicantly accelerated OSC research (chemical structures shown in Fig. S1 in the ESI †), [17][18][19][20] and the power conversion efficiencies (PCEs) of the state-of-the-art devices have surpassed 19%.…”
Section: Introductionmentioning
confidence: 99%
“…In general, D cores can be divided into two categories: fused-ring cores, such as ITIC, 3 Y6 and their derivatives, 6,7,23 and non-fused cores. 24 IC-acceptor based fused-ring cores represent the highest performance in OSCs due to the controlled microstructures via large conjugated backbones as well as large steric hindrance, but their high synthetic complexity enhances the cost toward manufacture. As an alternative, researchers have used non-fused cores as the D segment to construct electron acceptors, such as by using electron-rich phenyl, [25][26][27][28][29] thienyl, [30][31][32][33] benzodithiophene, 34,35 etc., and electron-withdrawing benzothiadiazole, 2,[36][37][38] thienopyrroledione, 39,40 benzotriazole, 26 quinoxaline, 41 etc.…”
Section: Introductionmentioning
confidence: 99%